PENGARUH APLIKASI BIOCHAR DAN MIKORIZA TERHADAP KETAHANANAN CEKAMAN KEKERINGAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt) - Yoke I. Benggu; Syukur S. Gea; Lily. F Ishaq; Anthonius S. J. Adu Tae (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2021)
East Nusa Tenggara is a classified as semi-arid with short rainy month and the soil is generally less fertile. One of the land management efforts with existing condition is the application of biochar and mycorrhizae. The aims of this study were to investigate the effect of biochar combined with mycorrhizae to incrase maize resistance to drought and yield of maize. This study was designed in a randomized block design (RBD) with 12 treatments including; Biochar + AMF daily watering, Biochar + AMF every two days watering, Biochar every three days watering, Biochar daily watering, Biochar every two days watering, biochar every three days watering, AMF daily watering, AMF every two days watering, AMF every three days watering, Without Biochar and without AMF daily watering, Without Biochar and without AMF every two days watering, and Without Biochar and without AMF every three days watering. There were three replicates for each treatment. Variables observed were soil water content, organic C, total-N, available P, exchangeable K, weight of cobs without cornhusk and weight of cobs with cornhusk The results showed that the application of biochar and mycorrhizae with daily watering had a significant effect on cob weight without cornhusk. The application of biochar and AMF gave better soil water content, total N, available P, exchangeable K, and cob weight with and without cornhusk compared to the treatment without biochar and wthout AMF